Addition type liquid silicone rubber material for transparent heat insulation and preparation method of addition type liquid silicone rubber material

By coating transparent heat-insulated addition-shaped liquid silicone rubber material on the window, functional tungsten oxide powder regulates the absorption and reflection of solar radiation, the high energy consumption problem caused by window materials is solved and efficient transparent heat-insulation effect is achieved.

CN119775780AInactive Publication Date: 2025-04-08HUBEI XINGRUI SILICON MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411842211.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-04-08
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing window materials have high energy consumption in buildings due to their high thermal conductivity and thermal radiation characteristics, especially the energy loss through windows accounts for 40% of the total energy consumption of buildings.

Method used

The transparent heat-insulated addition-shaped liquid silicone rubber material is used to coat or apply film on the window, and the redox process is performed under light excitation by using functional tungsten oxide powder to regulate the near-infrared transmittance of the material and achieve selective absorption and reflection of solar radiation.

Benefits of technology

The material can maintain high visible light transparency under high temperature and light conditions, while significantly reducing near-infrared transmittance, effectively reducing building energy consumption, reducing air conditioning load, and maintaining excellent mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides transparent heat-insulation addition type liquid silicone rubber and a preparation method thereof.The silicone rubber comprises a component A and a component B. The component A comprises 100 parts of base rubber and 0.01-4 parts of a platinum catalyst, the component B is prepared from 100 parts of base rubber, 15 to 30 parts of vinyl-containing branched polysiloxane, 6 to 15 parts of methyl-terminated linear polysiloxane, 0.5 to 10 parts of cross-linking agent and 3 to 6 parts of inhibitor; the base rubber is prepared from 100 parts of alpha, omega-divinyl polydimethylsiloxane, 10 to 50 parts of white carbon black, 2 to 20 parts of heat-insulating functional powder, 6 to 30 parts of structured control agent and 1 to 10 parts of water. The prepared silicone rubber has high visible light transmittance, the near-infrared transmittance can be dynamically regulated and controlled, and the transparent heat insulation or heat preservation effect is achieved. Compared with a common addition type silicone rubber material, the addition type silicone rubber material has lower heat conductivity, the method is simple in process and low in cost, and the prepared composite material is excellent in performance and free of pollution to the environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of silicone rubber and its application, and in particular relates to a transparent heat-insulating addition-type liquid silicone rubber material and a preparation method thereof. Background Art

[0002] The energy loss through windows in buildings can account for 40% of the total energy consumption of buildings. How to reduce energy waste in buildings and achieve the goals of energy conservation, emission reduction and environmental protection is also a problem of great concern to the world. Ordinary windows have high thermal conductivity and thermal radiation performance. Heat is transferred through windows, which has complex energy dissipation problems. It is necessary to solve the problems of excessive emissivity and thermal conductivity of building window glass from the root. With the improvement of people's living standards, while pursuing a more comfortable life and living environment, heating and ventilation facilities have also become an important part of buildings, but there are still serious energy loss and waste problems in this process. With the continuous acceleration of social development, people's demand for energy is also increasing. How to reduce energy waste, reduce the energy loss of buildings as much as possible, create a comfortable and low-energy living environment, and achieve the goals of energy conservation, emission reduction and environmental protection.

[0003] In order to create a comfortable indoor environment in buildings, a large amount of energy will be consumed for artificial lighting, heating and cooling, and ventilation. As an important channel connecting the indoor and outdoor environments, windows play an important role in building structures, ensuring indoor lighting, ventilation, noise control, and indoor and outdoor interaction. Compared with other structural components in buildings, windows have higher thermal conductivity and thermal radiation characteristics, and heat can be more easily transferred through windows. They also face complex and severe energy dissipation problems. It is estimated that energy loss through windows accounts for 40% of the total energy consumption of buildings. Simply reducing energy consumption by reducing the area of ​​windows will affect human health and work efficiency. In order to pursue comfort and beauty, windows account for an increasing proportion of modern building exterior walls, which also leads to increasing energy losses through windows. Therefore, it is of great practical significance to improve the energy efficiency of windows through energy-saving transformation, which can reduce the energy loss caused by windows, thereby reducing building energy consumption and achieving the goal of energy conservation and emission reduction.

[0004] There are usually three ways to transfer heat: thermal radiation, thermal conduction and thermal convection. Buildings also transfer heat in these three ways. The way windows transfer heat by thermal radiation mainly includes direct solar radiation and thermal radiation from surrounding objects. The spectrum of solar radiation on the earth's surface is mainly concentrated in the range of 300-2500nm. According to the energy distribution, there are 5% ultraviolet light (UV, 300-400 nm), 43% visible light (Vis, 400-700 nm) and 52% near infrared light (NIR, 700-2500 nm). Visible light is the main source of natural lighting, and other bands of spectrum are basically not perceived by the human eye. Windows use solar heat for indoor heating while using natural lighting, but excessive solar heat radiation brought by windows will make the indoor temperature too high, resulting in the use of air conditioning and refrigeration, which increases energy consumption. Buildings in hot areas need to reduce the entry of near infrared and ultraviolet light into the room as much as possible while ensuring natural lighting, in order to achieve better transparent insulation effect. According to Kirchhoff's law, when the temperature of an object is greater than 0 K, it will continuously radiate energy to the surrounding environment by emitting long-wave infrared rays. Therefore, in summer, the solar radiation that enters the room through the windows will increase the temperature of indoor objects; in winter, indoor objects radiate heat to the outside, and most of the heat radiation absorbed by the windows will be radiated to the outside, which increases the energy consumption in the building. First, ordinary glass has a high thermal emissivity (the emission of ordinary glass is 0.85). In hot or cold environments, if the heat from solar radiation entering the room can be blocked or retained, the energy consumption of artificial cooling or heating can be further reduced. This requires windows to have a low emissivity, which can block most of the heat radiation from the outside or reflect it back into the room. Second, the main material of the window is inorganic glass. Ordinary single-layer glass has a high thermal conductivity (1 W·m -1 ·K -1 ), causing heat to be easily exchanged by conduction.

[0005] At present, researchers use static temperature control materials such as heat-reflective films and low-emissivity films, as well as dynamic temperature control materials such as thermochromics, photochromics, electrochromics, and aerochromics. By changing the proportion of solar radiation energy entering the room through temperature control materials, and suppressing conduction and convection between indoor and outdoor by reducing the thermal conductivity of windows, they can significantly save energy consumption in buildings. The widely studied low thermal conductivity materials are mainly silica aerogel and transparent wood. The rich pore structure produced during the preparation of silica aerogel has extremely low thermal conductivity, but this type of structure will cause strong light scattering and affect the transparency of the material; while the microchannel structure in transparent wood brings excellent thermal insulation performance, the presence of channels and pigments will also make it opaque to visible light. In general, adjusting thermal conductivity has a high energy-saving effect on temperature control materials, and the balance between low thermal conductivity and high visible light transparency is still a key problem that needs to be solved. The silicon atoms on the silicone rubber molecules are simultaneously connected to oxygen and organic groups such as methyl and vinyl. Therefore, it has the characteristics of both organic and inorganic materials, and has excellent properties such as good high temperature resistance, low temperature resistance, electrical insulation, physiological inertness and aging resistance. It is widely used in various fields such as medical, infant, electricity and daily life.

[0006] In summary, we disclose a method for preparing a transparent heat-insulating addition-type liquid silicone rubber material, which is applied to windows by coating or mounting to reduce the energy loss problem caused by windows in buildings. Summary of the invention

[0007] The purpose of the present invention is to provide a transparent heat-insulating addition-type liquid silicone rubber material and a preparation method thereof in order to overcome the deficiencies of the above-mentioned prior art.

[0008] A transparent heat-insulating addition-type liquid silicone rubber, comprising, by mass fraction, a component A and a component B, wherein the component A comprises 100 parts of a base rubber and 0.01-4 parts of a platinum catalyst, and the component B comprises 100 parts of a base rubber, 15-30 parts of a vinyl-branched polysiloxane, 6-15 parts of a methyl-terminated linear polysiloxane, 0.5-10 parts of a crosslinking agent, and 3-6 parts of an inhibitor; The base glue comprises 100 parts of α, ω-divinyl polydimethylsiloxane, 10-50 parts of white carbon black, 2-20 parts of heat insulation functional powder, 6-30 parts of structuring control agent and 1-10 parts of water.

[0009] The white carbon black is precipitated white carbon black or fumed white carbon black, and the specific surface area of ​​the fumed white carbon black is 200-400 m 2 / g.

[0010] The heat-insulating functional powder is at least one of vanadium dioxide, tungsten oxide and related modified powder materials.

[0011] The structuring control agent comprises an organosilazane or an organosiloxane, preferably at least one of hexamethyldisilazane, tetramethyldivinylsilazane, methyltrimethoxysilane, dimethyldiethoxysilane or dimethylvinylethoxysilane.

[0012] The cross-linking agent is a methyl hydrogen-containing polysiloxane containing more than three silicon-hydrogen bonds in each molecule, wherein the mass fraction of hydrogen is 0.1%-1.6%.

[0013] The inhibitor is at least one of tetramethyldivinyldisiloxane, ethynylcyclohexanol, methylbutynol or tetramethyltetravinylcyclotetrasiloxane.

[0014] The platinum catalyst is a Karlstedt catalyst, which is a chloroplatinic acid tetramethyldisiloxane complex, and the concentration of the platinum catalyst is 2000-5000 ppm.

[0015] The mass percentage of vinyl in the vinyl-containing branched polysiloxane is 1%-10%, and the viscosity is 200mPa·s-80000mPa·s; the viscosity of the methyl-terminated linear polysiloxane is 3mPa·s-15000mPa·s.

[0016] A method for preparing a transparent heat-insulating addition-type liquid silicone rubber comprises the following steps: S1. Preparation of base glue: S11. The structuring control agent and water are sequentially added to the α, ω-divinyl polydimethylsiloxane and stirred to mix; S12 then add white carbon black 6-10 times, stirring to mix evenly; S13. Add the heat-insulating functional powder in 1-3 portions, stir and mix, and control the temperature at 40-60°C; S14. The temperature rises to 100-120°C and stirring continues; S15. The temperature is raised to 140-160°C and stirring is continued under vacuum conditions; S16 cooling the material to obtain a base rubber; S2. Preparation of component A and component B: Add the platinum catalyst to the base rubber, evacuate and stir, and finally filter the mixture to obtain component A; Add vinyl branched polysiloxane, methyl terminated linear polysiloxane, crosslinking agent and inhibitor into the base rubber, evacuate and stir, and finally filter the mixture to obtain component B.

[0017] The stirring time of S13 is 0.5-6 h; the stirring time of S14 and S15 is 1-6 h; the vacuum pressure of S15 is -0.08MPa to -0.098MPa; the vacuum stirring time of S2 is 1-4 h, and the vacuum pressure is -0.06MPa to -0.08MPa.

[0018] The beneficial effects of the present invention are as follows: The heat-insulating functional powder / silicone rubber composite material is prepared by a stirring and dispersing method, and functional tungsten oxide powder is added. The reversible redox process of the tungsten oxide material under light excitation causes a reversible change in the optical properties of the tungsten oxide material. The heat-insulating functional filler is compounded into the liquid silicone rubber material. When the ambient temperature is higher than the phase transition temperature of the material, the material can have a high visible light transmittance while the near-infrared transmittance is reduced. When the ambient temperature is lower than the phase transition temperature, an oxidation reaction occurs to increase the transmittance of the material in the near-infrared band. During this change process, the high transparency of the visible light band can be maintained, and the solar spectrum is selectively absorbed, achieving static or dynamic spectral selective regulation of solar radiation, and achieving the effect of transparent heat insulation or heat preservation. Compared with ordinary addition-type silicone rubber materials, the present invention has lower thermal conductivity, the method is simple in process, low in cost, and the prepared composite material has excellent performance and is pollution-free to the environment. DETAILED DESCRIPTION

[0019] The embodiments of the present invention will be described in detail below with reference to examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.

[0020] Preparation method of transparent heat-insulating silicone rubber material: S1. Preparation of base glue: S11. The structuring control agent and water are sequentially added to α, ω-divinyl polydimethylsiloxane and stirred to mix; S12 then added white carbon black 6 times on average, stirring to mix evenly; S13. Add the heat insulation functional powder in 3 equal portions, stir and mix, control the temperature at 60°C, and stir for 0.5h; S14. The temperature was raised to 120°C and stirring was continued for 1h; S15. The temperature was raised to 160°C and stirring was continued for 1 h under vacuum conditions with a vacuum pressure of -0.08 MPa; S16 cooling the material to obtain a base rubber; S2. Preparation of component A and component B: Add platinum catalyst to the base rubber, stir under vacuum for 1 hour, and finally filter the mixture to obtain component A. The vacuum pressure is -0.08MPa; Add vinyl-branched polysiloxane, methyl-terminated linear polysiloxane, crosslinking agent and inhibitor into the base rubber, stir under vacuum for 1 hour, and finally filter the mixture to obtain component B. The vacuum pressure is -0.06 MPa.

[0021] The basic properties of the materials involved in the following examples and comparative examples are as follows: Vinyl silicone oil: α, ω-divinyl polydimethylsiloxane, linear polysiloxane with a vinyl content of 0.08% by mass and a viscosity of 60000 mPa·s; Silazane treating agent: tetramethyl divinyl silazane; Thermal insulation functional powder: tungsten oxide; Platinum catalyst: complex of chloroplatinic acid and divinyltetramethyldisiloxane, concentration 3000ppm; Branched polysiloxane: the mass percentage of vinyl group is 3%, and the viscosity is 30000 mPa·s; Methyl terminated linear polysiloxane: viscosity 1000 mPa·s; Example 1 Base glue: 100 parts of vinyl silicone oil, 25 parts of reinforcing filler, 6 parts of silazane treatment agent, 2 parts of thermal insulation functional powder tungsten oxide, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​200m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane, with a concentration of 3000ppm; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane, 8 parts of methyl-terminated linear polysiloxane, 6 parts of crosslinking agent, and 4 parts of inhibitor, wherein the crosslinking agent is a linear polysiloxane with a mass percentage of hydrogen of 0.8% (viscosity of 50 mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0022] Example 2 Base glue: 100 parts of vinyl silicone oil, 25 parts of reinforcing filler, 6 parts of silazane treatment agent, 2 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​300m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0023] Example 3 Base glue: 100 parts of vinyl silicone oil, 25 parts of reinforcing filler, 6 parts of silazane treatment agent, 2 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​380m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0024] Example 4 Base glue: 100 parts of vinyl silicone oil, 25 parts of reinforcing filler, 9 parts of silazane treatment agent, 2 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​380m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0025] Example 5 Base glue: 100 parts of vinyl silicone oil, 25 parts of reinforcing filler, 9 parts of silazane treatment agent, 4 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​380m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 250mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0026] Example 6 Base glue: 100 parts of vinyl silicone oil, 25 parts of reinforcing filler, 6 parts of silazane treatment agent, 6 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​380m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0027] Example 7 Base glue: 100 parts of vinyl silicone oil, 30 parts of reinforcing filler, 6 parts of silazane treatment agent, 4 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​380m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0028] Example 8 Base glue: 100 parts of vinyl silicone oil, 35 parts of reinforcing filler, 6 parts of silazane treatment agent, 4 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​380m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.8% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0029] Example 9 Base glue: 100 parts of vinyl silicone oil, 30 parts of reinforcing filler, 9 parts of silazane treatment agent, 4 parts of heat insulation functional powder, 2 parts of water, among which the reinforcing filler has a specific surface area of ​​300m 2 / g of fumed silica; Component A: 50 parts of base rubber, 2 parts of platinum catalyst, wherein the platinum catalyst is a complex of chloroplatinic acid and divinyltetramethyldisiloxane; Component B: 80 parts of base rubber, 16 parts of branched polysiloxane with a vinyl content of 3%, 8 parts of methyl-terminated linear polysiloxane with a viscosity of 5mPa·s, 6 parts of cross-linking agent, and 4 parts of inhibitor, wherein the cross-linking agent is a linear polysiloxane with a hydrogen content of 0.07% (viscosity of 50mPa.s), and the inhibitor is tetramethyldivinyldisiloxane.

[0030] Comparative Example 1 This comparative example is based on Example 9, except that the component of the heat-insulating functional powder is deleted, and the remaining formula components and preparation method are the same as those of Example 9.

[0031] Comparative Example 2 This comparative example is based on Example 9, except that the amount of the platinum catalyst is adjusted to 4 parts, and the remaining formula components and preparation method are the same as those of Example 9.

[0032] Comparative Example 3 This comparative example is based on Example 9, except that the amount of the inhibitor is adjusted to 2 parts, and the remaining formulation components and preparation method are the same as those of Example 9.

[0033] For both the examples and the comparative examples, a base rubber was prepared separately, and then component A and component B were prepared, and then component A and component B were mixed in a weight ratio of 1:1 to obtain an addition type liquid silicone rubber, and the viscosity of the addition type liquid silicone rubber was tested. Furthermore, the addition type liquid silicone rubber was cured at 140°C for 10 minutes, and then subjected to secondary vulcanization treatment at 200°C for 4 hours to obtain a silicone rubber elastomer. The silicone rubber elastomer was tested, and the test method was as follows: Transmittance: The transmittance at 560nm in the visible light band was tested using a UV-Visible / NIR spectrophotometer from Japan's HITACHI company.

[0034] Shore A hardness: GB / T2794-2013; Tensile strength: GB / T531-1999; Elongation at break: GB / T528-2009; Tear strength: GB / T529-2008; △Tsol test method: Calculated after testing using the UV-Visible / NIR spectrophotometer of Japan's HITACHI company. The calculation formula is as follows:

[0035] △T sol =T vsi- T NIR In the formula, T vis is the average transmittance of visible light (380-780nm), T NIR is the average transmittance of near infrared (780-2500nm), where S (λ) is the relative spectral distribution of the solar spectrum passing through 1.5 times the vertical atmospheric thickness, where T (λ) is the spectral transmittance of the test sample, △T sol is the dimming coefficient of near infrared shielding performance.

[0036] The performance results of the transparent heat-insulating silicone rubber materials prepared in the above Examples 1 to 9 and Comparative Examples 1 to 3 are shown in Table 1.

[0037] Table 1 Transparent heat-insulating liquid silicone rubber material performance results list

[0038] It can be seen from the performance test results that the low-transparency thermal insulation liquid silicone rubber material prepared in this application can meet the needs of transparent thermal insulation. The overall transmittance of the implementation sample is above 83%, the thermal conductivity is in the range of 0.25-0.35, and the mechanical properties are maintained at a high level, which can meet the strength requirements of the material in the application.

[0039] In the above embodiment, the material has no significant effect on the transmittance of visible light before and after the phase change under the influence of factors such as temperature and light, but has a great influence on the transmittance of near-infrared light. After the phase change occurs under the influence of factors such as outdoor ambient temperature and light, the dimming coefficient △Tsol of the prepared heat-insulating silicone rubber material is large, which indicates that when the light is strong and the ambient temperature is high, the material has high barrier properties to near-infrared light. When used as a window coating, it can block near-infrared radiation from entering the room, reduce the air conditioning load, and significantly save the energy consumption of the building by changing the proportion of solar radiation energy entering the room and suppressing the conduction convection between indoor and outdoor by reducing the thermal conductivity of the window. By comparing Example 1 with Example 3, the addition of white carbon black with different specific surface areas has a great influence on the mechanical and optical properties of the material. The transmittance and tensile tearing mechanical properties of Example 3 are much higher than those of Example 1. This is because 380m 2 / g specific surface area of ​​white carbon black relative to 200m 2 / g white carbon black has a smaller particle size and has better transparency after being dispersed in silicone rubber. It has a more significant reinforcement effect on silicone rubber, and its transmittance and mechanical properties will be improved.

[0040] By comparing Example 3 with Example 4, adding white carbon black with the same specific surface area can slightly improve the light transmittance of the silicone rubber when the amount of the structural control agent silazane is increased. This is because increasing the amount of silazane to modify the white carbon black can make the white carbon black and silicone oil have better compatibility, better dispersion and improved transparency.

[0041] By comparing Example 1 with Example 9, without adding heat-insulating functional powder, the dimming coefficient △Tsol of the material drops to 40%, and this surface tungsten oxide powder material has good near-infrared regulation characteristics.

Claims

1. A transparent heat-insulating addition-type liquid silicone rubber, characterized in that: The composition comprises component A and component B, wherein component A comprises 100 parts of a base gum and 0.01-4 parts of a platinum catalyst, and component B comprises 100 parts of a base gum, 15-30 parts of a vinyl branched polysiloxane, 6-15 parts of a methyl-terminated linear polysiloxane, 0.5-10 parts of a crosslinking agent, and 3-6 parts of an inhibitor. The base glue comprises 100 parts of α, ω-divinyl polydimethylsiloxane, 10-50 parts of white carbon black, 2-20 parts of heat insulation functional powder, 6-30 parts of structuring control agent and 1-10 parts of water.

2. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The white carbon black is precipitated white carbon black or fumed white carbon black, and the specific surface area of ​​the fumed white carbon black is 200-400 m 2 / g.

3. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The heat-insulating functional powder is at least one of vanadium dioxide, tungsten oxide and related modified powder materials.

4. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The structuring control agent comprises an organosilazane or an organosiloxane, preferably at least one of hexamethyldisilazane, tetramethyldivinylsilazane, methyltrimethoxysilane, dimethyldiethoxysilane or dimethylvinylethoxysilane.

5. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The cross-linking agent is a methyl hydrogen-containing polysiloxane containing more than three silicon-hydrogen bonds in each molecule, wherein the mass fraction of hydrogen is 0.1%-1.6%.

6. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The inhibitor is at least one of tetramethyldivinyldisiloxane, ethynylcyclohexanol, methylbutynol or tetramethyltetravinylcyclotetrasiloxane.

7. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The platinum catalyst is a Karlstedt catalyst, which is a chloroplatinic acid tetramethyldisiloxane complex, and the concentration of the platinum catalyst is 2000-5000 ppm.

8. The transparent heat-insulating addition-type liquid silicone rubber according to claim 1, characterized in that: The mass percentage of vinyl in the vinyl-containing branched polysiloxane is 1%-10%, and the viscosity is 200mPa·s-80000mPa·s; the viscosity of the methyl-terminated linear polysiloxane is 3mPa·s-15000mPa·s.

9. A method for preparing a transparent heat-insulating addition-type liquid silicone rubber, characterized in that: The following steps are involved: S1. Preparation of base glue: S11. The structuring control agent and water are sequentially added to the α, ω-divinyl polydimethylsiloxane and stirred to mix; S12 then add white carbon black 6-10 times, stirring to mix evenly; S13. Add the heat-insulating functional powder in 1-3 portions, stir and mix, and control the temperature at 40-60°C; S14. The temperature rises to 100-120°C and stirring continues; S15. The temperature is raised to 140-160°C and stirring is continued under vacuum conditions; S16 cooling the material to obtain a base rubber; S2. Preparation of component A and component B: Add the platinum catalyst to the base rubber, evacuate and stir, and finally filter the mixture to obtain component A; Add vinyl branched polysiloxane, methyl terminated linear polysiloxane, crosslinking agent and inhibitor into the base rubber, evacuate and stir, and finally filter the mixture to obtain component B.

10. The method for preparing the transparent heat-insulating addition-type liquid silicone rubber according to claim 9, characterized in that: The stirring time of S13 is 0.5-6 h; the stirring time of S14 and S15 is 1-6 h; the vacuum pressure of S15 is -0.08MPa to -0.098MPa; the vacuum stirring time of S2 is 1-4 h, and the vacuum pressure is -0.06MPa to -0.08MPa.

Citation Information

Patent Citations

  • Transparent nano thermal-insulating coating

    CN107573844A

  • Infrared adjusting transparent polysiloxane aerogel as well as preparation method and application thereof

    CN116804119A

  • Addition type liquid silicone rubber and preparation process thereof

    CN117363028A